Surrogacy and uterus transplantation using live donors: Examining the options from the perspective of ‘womb-givers’ - Mullock, Alexandra (Bioethics, 2021)
For females without a functioning womb, the only way to become a biological parent is via assisted gestation—either surrogacy or uterus transplantation (UTx). This paper examines the comparative impact of these options on two types of putative ‘womb-givers’: people who provide gestational surrogacy and those who donate their uterus for live donation. The surrogate ‘leases’ their womb for the gestational period, while the UTx donor donates their womb permanently via hysterectomy. Both enterprises involve a significant degree of self-sacrifice and medical risk in order to enable another person(s) to become a parent by either providing gestational labour or enabling the other person to undertake gestation themselves. In this paper, we explore the burdens and the benefits from the perspective of the womb-giver in order to inform ethical debate about assisted gestation. This is a perspective that is often neglected in the bioethical discourse. With both surrogacy and UTx, when success follows the womb-giver’s sacrifice, the key benefit is delivered to the intending parent(s), but as this article examines, the womb-giver may also enjoy some unique (relational) benefits as a result of their sacrifice. Ultimately, the choice of how a womb-giver lends assistance in gestation will impact on their bodily autonomy; some will prefer to carry a pregnancy and others to donate their uterus. We argue that the perspective of the womb-giver is crucial and thus far has not been afforded sufficient consideration in ethical discussion.